Insight into the nitrogen-doped carbon as oxygen reduction reaction catalyst: The choice of carbon/nitrogen source and active sites. (1st June 2016) - Zeng, Dongrong; Yu, Xiang; Zhan, Yunfeng; Cao, Linmin; Wu, Xiaoxian; Zhang, Bodong; Huang, Jilin; Lin, Zhipeng; Xie, Fangyan; Zhang, Weihong; Chen, Jian; Xie, Weiguang; et al.
Abstract: Nitrogen doped carbon material works as non-noble-metal catalyst for the oxygen reduction reaction. In this work the doping effect on two different carbon material by two different nitrogen sources is studied. The carbon material studied is self-prepared carbon ribbon with higher graphitization degree compared with commercial Vulcan XC72 carbon powder. NH3 and glycine are used as nitrogen sources which produce nitrogen containing functionalities after high temperature pyrolysis. NH3 doping of carbon ribbon has no positive effect on the ORR activity, while an obvious increase in the activity is found for the glycine doped carbon ribbon. The NH3 and glycine doped Vulcan carbon show similar activities which are better than undoped Vulcan carbon. The difference is explained by graphitization degree, nitrogen content and type of nitrogen containing functionalities. Highlights: The active sites of nitrogen doped carbon as ORR catalyst is studied. Nitrogen source can influence the ORR activity. Graphitization degree of carbon can influence the effect of nitrogen doping.